Genome-wide activities of Polycomb complexes control pervasive transcription - Lee, Hun-Goo; Kahn, Tatyana G.; Simcox, Amanda; Schwartz, Yuri B.; Pirrotta, Vincenzo

(untitled) (Genome Research, 2015)
Polycomb group (PcG) complexes PRC1 and PRC2 are well known for silencing specific developmental genes. PRC2 is a methyltransferase targeting histone H3K27 and producing H3K27me3, essential for stable silencing. Less well known but quantitatively much more important is the genome-wide role of PRC2 that dimethylates ∼70% of total H3K27. We show that H3K27me2 occurs in inverse proportion to transcriptional activity in most non-PcG target genes and intergenic regions and is governed by opposing roaming activities of PRC2 and complexes containing the H3K27 demethylase UTX. Surprisingly, loss of H3K27me2 results in global transcriptional derepression proportionally greatest in silent or weakly transcribed intergenic and genic regions and accompanied by an increase of H3K27ac and H3K4me1. H3K27me2 therefore sets a threshold that prevents random, unscheduled transcription all over the genome and even limits the activity of highly transcribed genes. PRC1-type complexes also have global roles. Unexpectedly, we find a pervasive distribution of histone H2A ubiquitylated at lysine 118 (H2AK118ub) outside of canonical PcG target regions, dependent on the RING/Sce subunit of PRC1-type complexes. We show, however, that H2AK118ub does not mediate the global PRC2 activity or the global repression and is predominantly produced by a new complex involving L(3)73Ah, a homolog of mammalian PCGF3.